Cognitive load management: Learning abstract and complex scientific concepts using visual metaphors and metonymies - Hindriana, Anna Fitri; Turki, Harith Ismael; Prihatin, Yoga; Setiawati, Ina; Abidin, Zaenal; Pratami, Alin Rizki (LPMPP Universitas Negeri Yogyakarta, 2026)
This study applies the principles of metaphors and metonymies in visual learning media to manage students’ cognitive load and enhance their comprehension of complex scientific concepts, specifically cell biology, in lower secondary education. Using the ADDIE (analysis, design, development, implementation, and evaluation) model, a 2D animated audio-visual learning media was developed and evaluated. The research explored the impact of the developed learning media on intrinsic, extraneous, and germane cognitive loads using questionnaires and pre-/post-tests with 303 participants (science teachers and lower secondary students) from five districts in West Java, Indonesia. Expert evaluations from linguistics, media, and science education specialists were also incorporated. The results indicate that the developed visual media is effective in facilitating information processing and meaning-making, leading to improved comprehension and retention of complex cell biology concepts. The use of metaphors and metonymies helped students connect abstract scientific concepts to familiar contexts, reducing extraneous cognitive load and promoting deeper understanding and concept retention. Overall, the findings suggest that visual media employing metaphors and metonymies can be a valuable tool for teaching highly abstract and complex scientific concepts.